Concussion and long‐term cognitive function among rugby players—The BRAIN Study. Issue 6 (20th October 2021) - Gallo, Valentina; McElvenny, Damien M.; Seghezzo, Giulia; Kemp, Simon; Williamson, Elizabeth; Lu, Kirsty; Mian, Saba; James, Laura; Hobbs, Catherine; Davoren, Donna; Arden, Nigel; Davies, Madeline; et al.
Abstract: Objective: The BRAIN Study was established to assess the associations between self‐reported concussions and cognitive function among retired rugby players. Methods: Former elite‐level male rugby union players (50+ years) in England were recruited. Exposure to rugby‐related concussion was collected using the BRAIN‐Q tool. The primary outcome measure was the Preclinical Alzheimer Cognitive Composite (PACC). Linear regressions were conducted for the association between concussion and PACC score, adjusting for confounders. Results: A total of 146 participants were recruited. The mean (standard deviation) length of playing career was 15.8 (5.4) years. A total of 79.5% reported rugby‐related concussion(s). No association was found between concussion and PACC (β –0.03 [95% confidence interval (CI): –1.31, 0.26]). However, participants aged 80+ years reporting 3+ concussions had worse cognitive function than those without concussion (β –1.04 [95% CI: –1.62, –0.47]). Conclusions: Overall there was no association between concussion and cognitive function; however, a significant interaction with age revealed an association in older participants.